Cloud Computing and Its Relationship to The Quality of Administrative Decisions Among Administrative Leaders in The Palestinian Ministry of Health in The Southern Governorates - Halalu, Eslam Esam; Abu Ghaben, Ahmed Farooq (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify cloud computing and its relationship to the quality of administrative decisions among administrative leaders in the Palestinian Ministry of Health in the southern governorates. The study population consisted of managers and heads of departments working in the Palestinian Ministry of Health whose number is (221) employees. The study sample was selected using the stratified random sample method, whose number is (141) employees. The questionnaire was also used as a main tool for collecting data, and the descriptive analytical approach as a research methodology. The study found that there was a large degree of approval for the use of cloud computing, with a high level of acceptability (71.13%), It was also found that there was a large degree of approval for the axis of the quality of administrative decisions, with a high level of acceptability (69.56%), It also indicated that there is a strong positive relationship with statistically significant between cloud computing and the quality of administrative decisions in the Palestinian Ministry of Health. The study recommended the necessity of the Palestinian Ministry of Health should pay more attention to using cloud computing and its various applications and software, and work to update technology services and applications continuously, and the need to keep pace with technological development in the field of cloud computing. and the development of training programs aimed at developing the capabilities of workers in the process of making and taking administrative decisions, and working on evaluating the administrative decisions taken periodically.